Voter Participation in the Covid-19 Pandemic: Evidence from Elections in Bengkalis Regency 2020 - Usman, Usman; Saeri, M.; Marta, Auradian (JOELS: Journal of Election and Leadership, 2023)
This study aims to describe and find out about the forms of voter participation in simultaneous regional head elections during the Covid 19 Pandemic Period in Bengkalis Regency in 2020. As well as to find out what are the factors that influence voter participation. This study uses a qualitative research method with a descriptive analysis method, as well as through a phenomenological approach, where this research can be started by paying attention to and examining the focus of the phenomenon to be examined, which looks at various subjective aspects of the object's behavior, namely the people in Bengkalis Regency who have the right to vote in the 2020 regional elections in accordance with the provisions of the law. The findings in this study are that community participation in the implementation of the 2020 regional head election during the Covid 19 pandemic in Bengkalis Regency increased by 11.50% when compared to the 2015 regional head election as well as the 2010 regional head election. The factors increasing community participation This is due to economic factors, the socialization factor of the organizers, the awareness factor of the voters themselves and also the first time voters, the political trust factor, the trust factor in the candidates, and the mobilization factor carried out by the candidates through the winning team, campaign team, and so on to the people in Bengkalis Regency. However, from all of these factors, based on the results of the research conducted by the researchers, the main factor that led to an increase in voter turnout was money politics or gifts in other forms carried out by election participants.